2021
DOI: 10.1371/journal.pone.0247889
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of avian HEV antibodies in apparently healthy chickens in southwest Nigeria

Abstract: Avian hepatitis E virus (aHEV) is associated with hepatitis-splenomegaly syndrome, big liver and spleen disease and hepatic rupture haemorrhage syndrome. However, the knowledge about aHEV in commercial layer chickens in Nigeria is scarce. In this study, 460 serum samples obtained from 36 apparently healthy commercial layer chicken flocks in three states (Ogun, Osun and Oyo States) of southwestern Nigeria were analysed by enzyme linked immunosorbent assay for the presence of anti-aHEV immunoglobulin Y (IgY) ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the field, avian HEV is often isolated from broiler breeders and laying hens with clinical symptoms, such as increased mortality and decreased egg production ( Haqshenas et al, 2001 ; Billam et al, 2005 ; Agunos et al, 2006 ; Troxler et al, 2014 ). Decreased egg production has also been reported under experimental conditions ( Sun et al, 2020 ; Osamudiamen et al, 2021 ; Zhao et al, 2017 ). Therefore, there is an urgent need to elucidate the mechanism underlying avian HEV-induced reduction in egg production.…”
Section: Introductionmentioning
confidence: 69%
“…In the field, avian HEV is often isolated from broiler breeders and laying hens with clinical symptoms, such as increased mortality and decreased egg production ( Haqshenas et al, 2001 ; Billam et al, 2005 ; Agunos et al, 2006 ; Troxler et al, 2014 ). Decreased egg production has also been reported under experimental conditions ( Sun et al, 2020 ; Osamudiamen et al, 2021 ; Zhao et al, 2017 ). Therefore, there is an urgent need to elucidate the mechanism underlying avian HEV-induced reduction in egg production.…”
Section: Introductionmentioning
confidence: 69%
“…This could be simply due to the type of material studied, as in Nigeria apparently healthy chickens were examined, while in our study we had samples obtained from flocks with diminished performance. In a recent study, we reported that the seroprevalence of aHEV in chicken flocks was much higher in Poland (56.1%) compared to China (35.9%), whereas in southwest Nigeria 75% examined chicken flocks were positive for aHEV antibodies [ 13 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that aHEV is capable of causing subclinical infections [ 11 , 17 ]. Recent study from apparently healthy layer flocks from Nigeria indicate approximately 10% aHEV RNA prevalence, while 75% of the examined flocks show antibodies against aHEV [ 18 , 19 ]. This study assessed the prevalence of aHEV among Polish flocks.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, cases of human HEV outbreaks have been reported [ 30 , 31 ]. Further, serological evidence of HEV is known from swine, rabbits, goats, sheep, cattle [ 32 , 34 , 35 ], and a 14.6% seroprevalence of aHEV was recently reported in layer chickens in Nigeria [ 36 ]. Only one study conducted in Ogun and Lagos Statesfound aHEV RNA in chicken feces samples.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, HEV is associated with sporadic cases and outbreaks in humans [ 30 , 31 ] and serological evidence has been reported from swine, rabbits, goats, hares, sheep, cattle, and layer chickens [ 32 , 33 , 34 , 35 ]. Until recently, when aHEV seroprevalence of 14.6% was reported in commercial layer chickens in Southwestern Nigeria [ 36 ], there was no report of the detection of aHEV antibodies among the chicken population in Nigeria. Although Ogbolu and Obi [ 37 ] reported the presence of aHEV RNA from chicken fecal samples collected in a study conducted in Lagos and Ogun States, Nigeria, only a small number of samples were tested in that study and no information on the virus genotype was provided.…”
Section: Introductionmentioning
confidence: 99%